Wind-pattern circulation as a palaeogeographic indicator: Case study of the 1.5–1.6 Ga Mangabeira Formation, São Francisco Craton, Northeast Brazil - Bállico, M.; Scherer, C.; Mountney, N.; Souza, E.; Chemale, F.; Pisarevskiy, Sergei; Reis, A. (Elsevier BV, 2017)
The preserved deposits of dune-scale aeolian bedforms provide valuable palaeoenvironmental indicators of atmospheric circulation patterns and the latitudinal position and distribution of land masses. However, no attempts to use palaeowind directions and palaeogeographic reconstructions of ancient land mass distribution have been published to model Precambrian atmospheric circulation. The Mangabeira Formation is a large Mesoproterozoic aeolian erg succession (1.6–1.5 Ga) composed of two aeolian units that accumulated in the São Francisco Craton, Brazil. The Lower Unit records multiple drying-upward depositional cycles, each of which represents an episode of erg expansion and contraction driven by climate changes. The Upper Unit is composed dominantly of stacked aeolian dune strata that lack intervening interdune deposits and which record extreme aridity. Palaeowind directions recorded from cross-strata of transverse, crescentic aeolian dunes of the Lower and Upper Units record dune migration under the influence of two dominant winds that blew to the southeast and northwest. Analysis of these palaeowind data in relation to assessment of regional palaeogeographic reconstructions for the period 1.6–1.5 Ga reveals a correlation between atmospheric circulation and land mass distribution. At this time the São Francisco Craton was located between the mid-latitudes and the equatorial zone. The wind regime determined from analysis of dip azimuths of cross-strata of the Lower Unit (1.6–1.54 Ga) are consistent with a palaeogeographic position between 25° and 35° S. Analysis of cross-strata dip azimuths of the Upper Unit indicate northwest-directed palaeowinds and a dominant monsoonal wind pattern from 1.54 to 1.5 Ga. During this time the large land mass of the São-Francisco-Congo and Siberian cratons drifted northwards through the equatorial zone from palaeolatitude 30° S to 30° N.